Recycling cardiogenic artifacts in impedance pneumography. (May 2019) - Lu, Yao; Wu, Hau-tieng; Malik, John
Highlights: Cardiogenic artifacts commonly seen in biomedical measurements carry useful hemodynamic information. The cardiac signal may be isolated using the de-shape synchrosqueezing transform. Isolating the cardiogenic artifact clarifies the signal of interest and presents useful hemodynamic information to the medical professional. Abstract: Purpose: Biomedical sensors often exhibit cardiogenic artifacts which, while distorting the signal of interest, carry useful hemodynamic information. We propose an algorithm to remove and extract hemodynamic information from these cardiogenic artifacts. Methods: We apply a nonlinear time-frequency analysis technique, the de-shape synchrosqueezing transform (dsSST), to adaptively isolate the high- and low-frequency components of a single-channel signal. We demonstrate this technique's effectiveness by removing and deriving hemodynamic information from the cardiogenic artifact in an impedance pneumography (IP). Results: The instantaneous heart rate is extracted, and the cardiac and respiratory signals are reconstructed. Conclusions: The dsSST is suitable for generating useful hemodynamic information from the cardiogenic artifact in a single-channel IP. We propose that the usefulness of the dsSST as a recycling tool extends to other biomedical sensors exhibiting cardiogenic artifacts.